Molecular Insights Into Lysyl Oxidases in Cartilage Regeneration and Rejuvenation - Lin, Weiping; Xu, Liangliang; Li, Gang (Frontiers in Bioengineering and Biotechnology, 2020)
Articular cartilage remains among the most difficult tissues to regenerate due to its poor self-repair capacity. The lysyl oxidase family (LOX; also termed as protein-lysine 6-oxidase), mainly consists of lysyl oxidase (LO) and lysyl oxidase-like 1-4 (LOXL1-LOXL4), has been traditionally defined as cuproenzymes that are essential for stabilization of extracellular matrix, particularly cross-linking of collagen and elastin. LOX is essential in the musculoskeletal system, particularly cartilage. LOXs-mediated collagen cross-links are essential for the functional integrity of articular cartilage. Appropriate modulation of the expression or activity of certain LOX members selectively may become potential promising strategy for cartilage repair. In the current review, we summarized the advances of LOX in cartilage homeostasis and functioning, as well as copper-mediated activation of LOX and hypoxia-responsive signalling axis during recent decades, the molecular modulation signalling network controlling LOX expression, indicating that appropriate manipulation of bioavailability of copper or oxygen for hypoxia-responsive-signalling-directed LOX modulation, which is promising for clinically implications of cartilage regeneration in regenerative medicine and tissue engineering, as well as a potential therapeutic approach for cartilage rejuvenation. Therefore, targeting copper-mediated hypoxia-responsive signalling axis for LOX modulation through appropriate manipulation of copper and oxygen bioavailability is a promising approach for cartilage repair and rejuvenation.